2001
DOI: 10.1093/humrep/16.4.668
|View full text |Cite
|
Sign up to set email alerts
|

Circulating follistatin concentrations are higher and activin concentrations are lower in polycystic ovarian syndrome

Abstract: Familial polycystic ovarian syndrome (PCOS) has been proposed to be linked to a site near the follistatin gene. We studied the concentrations of circulating follistatin, activin A and inhibin B in well-characterized subjects with PCOS (n = 108) and controls without PCOS (n = 20). Mean (+/- SEM) concentrations of follistatin were higher (P < 0.05) in PCOS (0.27 +/- 0.03 ng/ml) than controls (0.15 +/- 0.02 ng/ml) and activin A were lower (P < 0.05) in PCOS (0.20 +/- 0.01ng/ml) than controls (0.24 +/- 0.02 ng/ml)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
1
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 31 publications
2
37
1
1
Order By: Relevance
“…Body weight has been shown to affect the follistatin level in women with PCOS (8); however, such an association between body weight and follistatin level was not found in another study (7). With regression analysis, in this study, we showed that the circulating follistatin level was still significantly associated with hsCRP in the PCOS and control groups after further adjustment for insulin sensitivity, BMI, and FAI.…”
contrasting
confidence: 65%
See 1 more Smart Citation
“…Body weight has been shown to affect the follistatin level in women with PCOS (8); however, such an association between body weight and follistatin level was not found in another study (7). With regression analysis, in this study, we showed that the circulating follistatin level was still significantly associated with hsCRP in the PCOS and control groups after further adjustment for insulin sensitivity, BMI, and FAI.…”
contrasting
confidence: 65%
“…Serum circulating follistatin levels have been reported to be higher in women with PCOS than in those without PCOS (7,8). However, no significant difference in follistatin concentrations was measured in follicular fluids between follicles obtained from healthy controls and those from women with PCOS (9).…”
mentioning
confidence: 89%
“…Given the marked inhibitory effect of activins and BMPs on thecal androgen production, it has also been suggested (Glister et al 2005) that compromised intraovarian activin and/or BMP signalling, perhaps due to overexpression or activity of extracellular BPs could by a contributory factor in polycystic ovarian syndrome (PCOS), a condition associated with ovarian androgen excess and impaired preovulatory follicle development (Mason 2000). Consistent with this notion, there have been several reports of raised circulating follistatin levels in women with PCOS (Norman et al 2001, Chen et al 2009). However, we are not aware of any evidence implicating altered expression of other extracellular BMP-BPs in the aetiology of PCOS.…”
Section: Bmp-binding Proteins and Follicle Developmentmentioning
confidence: 96%
“…Consequently a shift from an activin-dominant to an inhibin-dominant microenvironment occurs during follicle growth [76], which is impaired in some, but not all, PCOS follicles [77][78][79]. Moreover, low activin A levels and high follistatin levels in the circulation of some PCOS patients [80,81] correspond with diminished intrafollicular activin in prenatally Ttreated sheep [26] and activin β subunit responsiveness to steroid in neonatal mice [82]. These findings emphasize the further need to understand how TGFβ family members affect intraovarian paracrine signaling during fetal developmental programming.…”
Section: Impaired Follicle Growthmentioning
confidence: 99%